Measuring tidal deformations by laser altimetry. A performance model for the Ganymede Laser Altimeter. (November 2015) - Steinbrügge, G.; Stark, A.; Hussmann, H.; Sohl, F.; Oberst, J.
Abstract: Invaluable information about the interior of icy satellites orbiting close to the giant planets can be gained by monitoring the response of the satellite's surfaces to external tidal forces. Due to its geodetic accuracy, laser altimetry is the method of choice to measure time-dependent radial surface displacements from orbit. We present an instrument performance model with special focus on the capabilities to determine the corresponding tidal Love number h 2 and apply the model to the Ganymede Laser Altimeter (GALA) on board of the Jupiter Icy Moons Explorer (JUICE). Based on the instrument and spacecraft performance, we derive the range error and the measurement capabilities of the GALA instrument to determine the amplitude of the tide induced radial displacement of Ganymede's surface using the cross-over technique. We find that h 2 of Ganymede can be determined with an accuracy of better than 2% by using data acquired during the nominal mission. Furthermore, we show that this accuracy is sufficient to confirm the presence of a putative subsurface water ocean and, additionally, to constrain the thickness of the overlaying ice shell to ± 20km. Abstract : Highlights: The performance of the Ganymede Laser Altimeter (GALA) has been assessed. Ranging, orbit and pointing errors have been taken into account for the analysis. The error in the determination of h 2 is predicted to be 2%. An ocean can be detected and the ice I thickness can be constrained to ±20 km. Different scenarios, structural and rheological models are discussed.